Intergenerational transmission of lockdown consequences: prognosis of the longer-run persistence of COVID-19 in Latin America - Guido Neidhöfer; Nora Lustig; Mariano Tommasi (The Journal of Economic Inequality, 2021)
The shock on human capital caused by COVID-19 is likely to have long lasting consequences, especially for children of low-educated families. Applying a counterfactual exercise we project the effects of school closures and other lockdown policies on the intergenerational persistence of education in 17 Latin American countries. First, we retrieve detailed information on school lockdowns and on the policies enacted to support education from home in each country. Then, we use these information to estimate the potential impact of the pandemic on schooling, high school completion, and intergenerational associations. In addition, we account for educational disruptions related to household income shocks. Our findings show that, despite that mitigation policies were able to partly reduce instructional losses in some countries, the educational attainment of the most vulnerable could be seriously affected. In particular, the likelihood of children from low educated families to attain a secondary schooling degree could fall substantially.
Keywords: I24; I38; J62; 300; COVID-19; Lockdowns; Human capital; School closures; Intergenerational persistence; Education; Inequality; Latin America